The European revolutions, 1848-1851 - Sperber, Jonathan, 1952- (New York : Cambridge University Press, 2005)
Reaching from the Atlantic to Ukraine, from the Baltic to the Mediterranean, the revolutions of 1848 brought millions of people across the European continent into political life. Nationalist aspirations, social issues and feminist demands coming to the fore in the mid-century revolutions would reverberate in continental Europe until 1914 and beyond. Yet the new regimes established then proved ephemeral, succumbing to counter-revolution. In this second edition, Jonathan Sperber has updated and expanded his study of the European Revolutions between 1848-1851. Emphasizing the socioeconomic background to the revolutions, and the diversity of political opinions and experiences of participants, the book offers an inclusive narrative of the revolutionary events and a structural analysis of the reasons for the revolutions' ultimate failure. A wide-reaching conclusion and a detailed bibliography make the book ideal both for classroom use and for a general reader wishing a better knowledge of this major historical event.
Cover; Half-Title; Series Ttile; Title; Copyright; Contents; Illustrations; Preface to the second edition; Chronology of events; Introduction; 1 Society and social conflict in Europe during the 1840s; 2 The pre-revolutionary political universe; 3 The outbreak of revolution; 4 Varieties of revolutionary experience; 5 Polarization and confrontation; 6 The mid-century revolutions in European history; Bibliography; Short biographies; Index
Includes bibliographical references (pages 284-298) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Europe -- History -- 1848-1849.; Revolutions -- Europe -- History -- 19th century; Europe -- Histoire -- 1848-1849.; Révolutions -- Europe -- Histoire -- 19e siècle.; HISTORY; Revolutions; Europe; 1800-1899; History